Go Programming Language For Dummies - Lee, Wei-Meng (For Dummies, 2021)
Ready, set, program with Go! Now is the perfect time to learn the Go Programming Language. It's one of the most in-demand languages among tech recruiters and developers love its simplicity and power. Go Programming Language For Dummies is an easy way to add this top job skill to your toolkit. Written for novice and experienced coders alike, this book traverses basic syntax, writing functions, organizing data, building packages, and interfacing with APIs. Go-or GoLang, as it's also known-has proven to be a strong choice for developers creating applications for the cloud-based world we live in. This book will put you on the path to using the language that's created some of today's leading web applications, so you can steer your career where you want to Go! Learn how Go works and start writing programs and modules Install and implement the most powerful third-party Go packages Use Go in conjunction with web services and MySQL databases Keep your codebase organized and use Go to structure data With this book, you can join the growing numbers of developers using Go to create 21st century solutions. Step inside to take start writing code that puts data in users' hands.